2014
DOI: 10.1039/c4ob01143k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of meta and para-substituted aromatic sulfonate derivatives of polydentate phenylazaphosphinate ligands: enhancement of the water solubility of emissive europium(iii) EuroTracker® dyes

Abstract: Publisher's copyright statement:Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
83
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(83 citation statements)
references
References 28 publications
0
83
0
Order By: Relevance
“…For a given ligand system, isomorphic solid state products are common. A calorimetric study of the interaction of the lanthanide cations with Q [6] in aqueous formic acid confirmed that the values for the reaction enthalpies for the respective complexes are almost identical [64].…”
Section: Introductionmentioning
confidence: 53%
See 4 more Smart Citations
“…For a given ligand system, isomorphic solid state products are common. A calorimetric study of the interaction of the lanthanide cations with Q [6] in aqueous formic acid confirmed that the values for the reaction enthalpies for the respective complexes are almost identical [64].…”
Section: Introductionmentioning
confidence: 53%
“…Five complexes were isolated with all but the fifth, a Yb 3+ complex (see below), containing K + . Each capsule included a bound nitrate ion in its cavity (the cavity of Q [5] is too small to include a [ReO 4 ] − anion, contrasting with Q [6] which is able to include this anion -see discussion in Section 3). In the first four complexes the lanthanide ion is nine-coordinate with a capped square antiprismatic geometry.…”
Section: Coordination Of Lanthanides To Cucurbit[5]urilsmentioning
confidence: 99%
See 3 more Smart Citations